Vascular Damages in Rats Immunized by α1-Adrenoceptor Peptides - Zhou, Zihua; Liao, Yuhua; Li, Liudong; Wei, Fen; Wang, Bin; Wei, Yumiao; Wang, Min; Cheng, Xiang (Cellular & molecular immunology, 2008)
Autoantibodies against the α1-adrenoceptor which had agonist activity as norepinephrine might play roles in the progression of hypertension, but whether the autoantibodies could induce vascular remodeling as norepinephrine is not clear. In this paper, the models with antibodies against the α1-adrenoceptor were made by immunizing Wistar rats with the synthesized the second extracellular loop of α1-adrenoceptor peptides. The homo-age male Wistar rats received BSA in the same immunizing manner and male spontaneous hypertensive rats （SHR） were used as control. All the rats were raised for one year. The blood pressure and morphological changes of arteries were measured. In the end, despite the systolic blood pressure of immunized rats had no difference with normal control, the media thickness of aortas and ratio of media to lumen in the third-order arteries of mesenteric vasculature were increased in immunized rats. The observation with electron microscope showed that the mitochondria of vascular smooth muscle cells （VSMCs） had notable hyperplasia, and the interstitial collagen fibril was increased too. The effects of purified antibodies against α1-adrenoceptor on the proliferation of cultured VSMCs, and the expressions of c-jun, c-fos and α1-adrenoceptor were detected. The results showed that the antibodies could promote the proliferation of cultured VSMCs, and enhance the expression of c-jun both in vitro and in vivo. So we concluded that antibodies against the α1-adrenoceptor could contribute to vascular damages in rats by stimulating the growth of VSMCs which might be caused by the increased c-jun expression, and might play particular roles in the pathological changes of hypertension.